Analysis of Hardiness Mediation in the Implementation of Group Psychoeducation Therapy on the Tolerance Academic Distress of Final Year Students - Indah Lestari; DYP Sugiharto; Muhammad Japar; Mulawarman Mulawarman; Ashari Mahfud (Universitas Negeri Semarang, 2021)
This study aims to assess the existence of a mediating variable in the form of hardiness in the implementation of group psychoeducation therapy to increase tolerance for academic distress. The research method used was an experiment, a pretest-posttest control group design involving 16 final year students who were selected proposive sampling from 135 students. The results indicate that there is an indirect effect on the implementation of group psychoeducation therapy in increasing the tolerance for academic distress through hardiness as a positively related mediation. This effect was considered to be greater than the direct effect of the psychoeducation therapy group on tolerance for academic distress, although they were both positively related.